2018
DOI: 10.5946/ce.2017.043
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoscopy in the Management of Boerhaave Syndrome

Abstract: Cases and Techniques Library (CTL) E24Musala Carmen et al. Boerhaave syndrome treatment with an over-the-scope clip … Endoscopy 2015; 47: E24-E25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
0
13
0
11
Order By: Relevance
“…In patients with late presentation and in patients with non-endoscopic EP, the use of endoscopy as first-line therapy may be considered (Grade 2C). Although successful endoscopic management has been reported in select Boerhaave [8991] patients with minimal symptoms and signs of sepsis, concerns on patient safety warrant caution regarding first-line use of endoscopic treatment under such circumstances [71, 89]. Endoscopic stenting is a useful adjunct treatment tool in patients with persistent leakage following surgical treatment of EP [92].…”
Section: Methodsmentioning
confidence: 99%
“…In patients with late presentation and in patients with non-endoscopic EP, the use of endoscopy as first-line therapy may be considered (Grade 2C). Although successful endoscopic management has been reported in select Boerhaave [8991] patients with minimal symptoms and signs of sepsis, concerns on patient safety warrant caution regarding first-line use of endoscopic treatment under such circumstances [71, 89]. Endoscopic stenting is a useful adjunct treatment tool in patients with persistent leakage following surgical treatment of EP [92].…”
Section: Methodsmentioning
confidence: 99%
“…Which is the best way to approach BS is still a matter of debate: actual guidelines for thoracic esophageal perforation suggest an individualized approach to primary repair the tear, while for what concern specifically esophageal spontaneous rupture, most of the available studies considered the thoracotomy/thoracoscopic approach as the way of choice [9,[17][18][19][20][21]. Anyway, there is not any specific guidelines for BS: some case reports suggest that laparoscopy may be just as safe and effective [12,13]; lastly, some authors also reported conservative or endoscopic treatment: nevertheless, these are just a few studies involving patients with less severe clinical picture, so further researches are needed to better understand their feasibility in more challenging conditions [5,7]. In this case series, we present our 5 years' experience: in all patients, we choose to approach laparoscopically the esophageal tear; when necessary, afterwards we performed a thoracic lavage through left thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the aim of the treatment should be both repair the esophageal tear and control the mediastinal contamination: on these bases, different strategies have been proposed. The most diffuse approach is the surgical direct repair with placement of a thoracic drainage: recently, less invasive approaches have been suggested such as conservative and endoscopic treatments, but there are only a few case series reporting discouraging or inconstant results [5][6][7]; thus, at the moment, surgery remains the cornerstone of BS management.…”
Section: Introductionmentioning
confidence: 99%
“…11 Ongoing debates exist regarding best practices based on a patient's presenting clinical scenario, with the current literature suggesting that endoscopic therapy be reserved for early presenters, those with a defect less than 1 cm and without evidence of sepsis, thus indicating a promising role for endoscopy in a carefully selected population with Boerhaave syndrome. 15,16…”
Section: Discussionmentioning
confidence: 99%